2022
DOI: 10.1177/10105395221106629
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Handgrip Asymmetry With Impaired Health-Related Quality of Life Among Older Adults in South Korea: A Cross-Sectional Study Using National Survey Data

Abstract: This study aimed to examine the associations of handgrip strength (HGS) and asymmetry with health-related quality of life among South Korean older adults. We enrolled 7395 older adults from the Korea National Health and Nutrition Examination Survey. Health-related quality of life was measured using the EuroQol-5 Dimension. Weakness was defined as a HGS of <26 kg for men and <18 kg for women. Handgrip strength symmetry was defined as an HGS ratio of 0.9:1.1, and HGS asymmetry was defined as a ratio outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Moreover, in the current study, we found that 15.91% (Method A) and 20.65% (Method B) of individuals presented with comorbid forms of HGS weakness and HGS asymmetry, which differs slightly from previous studies. For example, a previous analysis that enrolled 330 community‐dwelling adults aged 55 and over reported that 12.1% of them exhibited weak and asymmetric HGS (K. K. Chen, Ho, & Chau, 2022), and another study that included 7395 older South Koreans reported a 10.22% incidence of this comorbid condition (Baek et al, 2022), while a study of 364 geriatrics outpatients aged ≥60 years reported the proportion was 21.43% (Lin et al, 2022). The slight differences between these results, apart from age, may be due to variations in factors such as the incidence of chronic disease incidence, geographical location, nutritional conditions, or lifestyle factors between the studies, together with the criteria used for determining HGS weakness and asymmetry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in the current study, we found that 15.91% (Method A) and 20.65% (Method B) of individuals presented with comorbid forms of HGS weakness and HGS asymmetry, which differs slightly from previous studies. For example, a previous analysis that enrolled 330 community‐dwelling adults aged 55 and over reported that 12.1% of them exhibited weak and asymmetric HGS (K. K. Chen, Ho, & Chau, 2022), and another study that included 7395 older South Koreans reported a 10.22% incidence of this comorbid condition (Baek et al, 2022), while a study of 364 geriatrics outpatients aged ≥60 years reported the proportion was 21.43% (Lin et al, 2022). The slight differences between these results, apart from age, may be due to variations in factors such as the incidence of chronic disease incidence, geographical location, nutritional conditions, or lifestyle factors between the studies, together with the criteria used for determining HGS weakness and asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…HGS abnormalities, including weak or asymmetric HGS, are common in older adults Minghui Weng and Jianlin Pu contributed equally to this article, and should be considered co-first authors of this article. (Baek et al, 2022;Li et al, 2018;. Both weak HGS and asymmetric HGS alone have been reported to be associated with poor future health outcomes among older adults, including limitations in the specific activities of daily living (Mahoney et al, 2022), elevated risks of falls and fractures (Dowling et al, 2023;Go et al, 2021), all-cause mortality (Li et al, 2018), and the incidence of neurological and psychiatric disorders (Z.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current findings of the study are also in line with the findings from previous studies reporting the associations between handgrip strength and HRQoL in older adults. For example, Baek, Kim, and Kim [ 20 ], by analyzing nationwide survey data, showed that weak handgrip strength and handgrip strength asymmetry (defined as a handgrip strength of >10% stronger on either hand) were associated with impaired HRQoL in older Korean adults. Kang, Lim, and Park [ 19 ] analyzed the 2015 KNHNES data and demonstrated that low handgrip strength correlated with poor HRQoL—especially mobility and pain/discomfort variables of the EQ-5D—in Korean adults aged 20 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, loss of muscle strength assessed by handgrip strength is associated with health conditions, sarcopenia, disability, impaired physical functioning, and cognitive decline in older adults [ 17 ]. Additionally, handgrip strength is a biomarker for a lower HRQoL in older populations [ 18 , 19 , 20 ] and cancer survivors [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%